Microalgae Growth in Qatar for CO2 Capture and Biodiesel Feedstock Production (Global Journals of Research in Engineering, 2012)
Demands for and prices of liquid petroleum fuels are increasing. This challenge is motivating the development of alternative fuels, like biodiesel from non-food sources. Microalgae are a promising source of oil feedstock for biodiesel. Growing microalgae indoors uses water, chemical nutrients, artificial lights, and energy for harvesting, drying and oil extraction. The economics would be greatly improved if microalgae are grown outdoors in a hot sunny climate where the light energy is free and the temperature is adequate for growth. Using non-potable water (such as available and free salt-water) would reduce the water footprint. Open pond systems have low capital and operating costs and are wellsuited for growing microalgae in salty water. The ideal location for growing microalgae outdoors is a non-arable land that cannot be used for agriculture (such as Qatar desert). The purpose of this research is to study the growth of salt-water microalgae outdoors in Qatar#x2019;s hot sunny environment and compare it to indoor growth. Three Dunaliella microalgae (Bardawil, Parva and Salina) were grown in Persian Gulf saltwater medium. A fish tank photobioreactor was used to simulate an open pond. Dunaliella Bardawil provided the highest microalgae oil feedstock for biodiesel production, with a production rate of 20 mg dry algae/L-day, an oil content of 5.7 g oil/100 g dry algae, and oil production rate of 1.14 mg oil/L-day. The operation had a carbon sequestration efficiency of 6.5% and a photosynthetic efficiency of 1.11%. Among the algae tested, Dunaliella Bardawil is the optimal candidate for growth in Qatar conditions using an open pond system.
Keywords: Demands for and prices of liquid petroleum fuels are increasing This challenge is motivating the development of alternative fuels; like biodiesel fro